2019
DOI: 10.1590/1678-9199-jvatitd-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Protein identification from the parotoid macrogland secretion of Duttaphrynus melanostictus

Abstract: Background: Bufonid parotoid macrogland secretion contains several low molecular mass molecules, such as alkaloids and steroids. Nevertheless, its protein content is poorly understood. Herein, we applied a sample preparation methodology that allows the analysis of viscous matrices in order to examine its proteins. Methods: Duttaphrynus melanostictus parotoid macrogland secretion was submitted to ion-exchange batch sample preparation, yielding two fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…The protein component, which is another typical active substance of TV, has been receiving growing attention. Most investigations have focused on the qualitative identification of proteins, and few publications displayed the total protein content of TVs [ 4 , 6 ]. Therefore, the total protein content of 28 TV samples from the four Bufo samples was determined by the Bradford method, and the results are shown in Figure 3 A and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protein component, which is another typical active substance of TV, has been receiving growing attention. Most investigations have focused on the qualitative identification of proteins, and few publications displayed the total protein content of TVs [ 4 , 6 ]. Therefore, the total protein content of 28 TV samples from the four Bufo samples was determined by the Bradford method, and the results are shown in Figure 3 A and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Only BgC and BrS samples were found to contain probable E3 ubiquitin-protein ligase makorin-2 with antitumor activity. It is worth noting that certain homologous proteins were identified as distinct entities due to the utilization of different databases [ 6 , 21 ]. For instance, we identified serpin B5 and serpin B8, while serpin B6 was reported previously [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingerophrynus biporcatus prefer primary forest habitat, but much less in secondary and degraded habitats (Iskandar, 1998;Kurniati, 2013) such as the upstream part of the Code River and some areas downstream, which have more dense riparian vegetation but also more dense household waste. Both toads have parotoid glands on their skin that could protect them from potential predators (e.g., x, y, z) and also microbial infections (Neerati & Yanamala, 2013;Mariano et al, 2019;Wulandari et al, 2013), which are likely to be found on disturbed areas or areas with many household wastes. Phrynoidis asper is commonly found in the upstream area (Subeno, 2018).…”
Section: Resultsmentioning
confidence: 99%